INOVASI PEMBELAJARAN MULOK DI SEKOLAH DASAR: PENGOLAHAN SUSU MENJADI ES KRIM - Mei Dwi Purwanti; Heru Subrata; Ari Metalin Ika Puspita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
ABSTRACT Processing milk into ice cream in elementary schools is an educational activity that is useful for improving students' knowledge and skills in the field of food science and technology. This research aims to introduce the simple process of milk processing and its application in making ice cream. The research method used was descriptive qualitative method, which includes teaching the theory of milk composition and basic principles of ice cream making, as well as hands-on practice. In this activity, students were invited to understand the nutritional content of milk and practice making simple ice cream using the colligative principle of solution (freezing point drop). The results showed that the colligative properties of the solution can accelerate the process of freezing milk into ice cream. Students can easily understand the basic concepts taught and are able to make ice cream. In addition, this program also increases students' interest in science and entrepreneurial skills. Through this activity, it is hoped that students will not only gain new knowledge, but also be motivated to be more creative and innovative in applying the knowledge they have learned in their daily lives.